ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN DALAM PENGIRIMAN BARANG PADA CV BUNGA BUANA DI KOTA TIMIKA - Nila Sagita Andul Mutalib; Siske Tontong (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study aims to examine the relationship between service quality, price and trust on customer loyalty through customer satisfaction at CV Bunga Buana in Timika. The data collected in this study comprises qualitative and quantitative data sourced from the freight forwarding company CV Bunga Buana in Timika. This study employs an associative research method, which is a type of research designed to identify relationships between two or more variables. The research techniques used include observational data collection and questionnaires. This is a quantitative study with a sample size of 100, and the method used for analysis is SEM utilising the Smart-PLS Version 4.0 software. The results of the analysis indicate that service quality has a positive and significant effect on customer satisfaction; price and trust have a positive and significant effect on customer satisfaction; customer satisfaction has a positive and significant effect on customer loyalty; trust and customer satisfaction have a positive but insignificant effect on customer loyalty; and service quality and price have a significant effect on customer loyalty via customer satisfaction.